Nasal administration of Lactobacillus rhamnosus CRL 1505 improves humoral immunity in malnourished mice - Barbieri, N. (2010)
We evaluated the effect of Lactobacillus rhamnosus CRL1505 (Lr05) nasal treatment on the recovery of humoral immune response in malnourished immunocompromised mice. Weaning mice were malnourished with protein free diet for 21d. Malnourished mice were fed a balanced conventional diet (BD) for 7 days or BD for 7 days with Lr05 nasal treatment on days 6 and 7 (BD+Lr05). On day 8 we studied B lymphocytes population in blood, spleen and bone marrow. Expression of B220 and HSA were determined by flow cytometry. Total lymphocytes counts and B220+HSA+ cells in BD+Lr05 mice were significantly higher than those in the BD group. To assess whether changes induced by BD+Lr05 treatment modifies the resistance to infection and the humoral immune response; we performed an intranasal challenge with Streptococcus pneumoniae (Sp). BD mice showed lung and blood positive cultures throughout the studied period. Treatment with BD+Lr05 increased resistance to infection, prevented the dissemination of Sp into blood and improved lung clearance. Levels of specific IgG in the serum of BD+Lr05 mice were higher than in the BD group. In addition, mice treated with BD+Lr05 showed higher levels of specific respiratory IgA. Nasal administration of Lr05 improved humoral immunity and increased resistance against Sp infection. Nasal treatments with lactic acid bacteria would be an interesting alternative to improve defenses in immunocompromised hosts.